Study on a thermosetting polyurethane modified asphalt suitable for bridge deck pavements: Formula and properties. (30th April 2020) - Zhang, Zengping; Sun, Jia; Jia, Meng; Qi, Bing; Zhang, Hongliang; Lv, Wenjiang; Mao, Zhiyong; Chang, Pengtao; Peng, Jiang; Liu, Yichen
Highlights: We prepare a novel thermosetting polyurethane modified asphalt binder. Formula and properties of TS-PU modified binders are determined. TS-PU modified asphalt is suitable for bridge deck pavements. TS-PU modified asphalt generally saves cost compared to epoxy binder. Abstract: High-cost and unsatisfactory flexibility generally reduce the application possibility of epoxy asphalt binders in bridge deck asphalt pavements. To solve these defects, a novel idea that develops a thermosetting polyurethane (TS-PU) modified asphalt binder is put forward in this work. First, the appropriate formula of the TS-PU modified binder is determined via a series of laboratory tests. The comprehensive properties of asphalt binders containing various TS-PU contents are then investigated. Finally, a performance comparison is made between the TS-PU modified binder (with the optimum TS-PU content), styrene-butadienestyrene (SBS) modified binder and epoxy modified binder. Results show that, the addition of TS-PU improves the high temperature and mechanical properties while impairs the low temperature property of base binder. It is also demonstrated in this study that, the TS-PU modified binder is much better in high temperature rutting resistance and tensile strength than SBS modified binder; meanwhile, the TS-PU modified binder, on the whole, has an advantage over epoxy modified binder in flexibility and cost saving, showing a favorable application prospect in bridge deck pavements.